To solve this problem using Hess's Law, we need to manipulate the given reactions in such a way that when they are added together, they will result in the desired reaction. First, we need to reverse the third reaction and multiply it by 2:2H2S g 4H2 g + 2S s H3' = +72 kJ/molNow, we need to subtract 2SO3 g from the second reaction to get 2SO2 g in the products:2SO3 g 2S s + 3O2 g H2' = +791 kJ/mol2SO3 g 2SO2 g + O2 g H4 = unknownSubtracting the second equation from the first:2S s + 2O2 g 2SO2 g H4 = -198 kJ/molNow, we can add the manipulated reactions together:2H2 g + O2 g 2H2O l H1 = -484 kJ/mol2H2S g 4H2 g + 2S s H3' = +72 kJ/mol2S s + 2O2 g 2SO2 g H4 = -198 kJ/mol---------------------------------------------2H2S g + 3O2 g 2H2O l + 2SO2 g H = ?Adding the enthalpy changes:H = H1 + H3' + H4H = -484 kJ/mol + 72 kJ/mol - 198 kJ/molH = -610 kJ/molSo, the enthalpy change for the given reaction is -610 kJ/mol.